Familial hypercholesterolaemia in patients with ischaemic stroke or transient ischaemic attack. (14th December 2017) - Toell, T.; Mayer, L.; Pechlaner, R.; Krebs, S.; Willeit, K.; Lang, C.; Boehme, C.; Prantl, B.; Knoflach, M.; Ferrari, J.; Fuchs, P.; Prokop, W.; et al.
Abstract : Background and purpose: Identification of patients with familial hypercholesterolaemia (FH) is a prerequisite for the appropriate management of their excess cardiovascular risk. It is currently unknown how many patients with acute ischaemic stroke or transient ischaemic attack (TIA) are affected by FH and whether systematic screening for FH is warranted in these patients. Methods: The prevalence of a clinical diagnosis of FH was estimated in a large representative series of patients with acute ischaemic stroke or TIA (ABCD2 score ≥ 3) using the Dutch Lipid Clinic Network Algorithm (DLCNA; possible FH ≥3, probable/definite FH ≥6). Results: Out of 1054 patients included in the present analysis, 14 had probable/definite FH (1.3%; 95% confidence interval 0.6–2.0) and 107 possible FH (10.2%; 8.4–12.0) corresponding to an overall prevalence of potential FH of 11.5%. Prevalences were even higher in patients with stroke/TIA manifestation before age 55 in men or 60 in women (3.1%, 0.6–5.6; and 13.1%, 8.3–17.9) and those with a prior history of cardiovascular disease (2.6%, 0.9–4.3; and 15.1%, 11.3–18.9). Of note, in two‐thirds of our patients with probable/definite and possible FH, stroke or TIA was the initial clinical disease manifestation. Conclusions: The frequency of potential FH, based on clinical criteria, in patients with acute ischaemic stroke or TIA was 11.5% and that of probable/definite FH (1.3%) was similar to recently reported counts for patients with acute coronary syndrome (1.6%). FH screening using the DLCNA is feasible in clinical routine and should be considered as part of the usual diagnostic work‐up. Abstract : Click here to view the accompanying paper in this volume.